ANALISIS DAN DESAIN SISTEM INFORMASI MANAJEMEN RESTORAN BERBASIS WEB STUDI KASUS PECEL KAWI HJ.MUSILAH - Ismawan, Puji; Cahyono, Dwi (Program Studi Informatika Universitas Teknologi Sumbawa, 2025)
This study analyzes and designs a web-based restaurant management information system for Pecel Kawi Hj. Musilah. Qualitative methods develop an application displaying menu, pricing, best-sellers, payment receipts and customer data. The system analyzes frequently ordered menus and generates monthly reports. Results show the web-based system enhances service efficiency, customer satisfaction and management ease. The Waterfall model addresses manual ordering issues. This research contributes to developing effective restaurant management information systems. Additionally, the system aids employees in data management and improves service quality, increasing revenue and customer satisfaction.